The Inheritance Verses: A Comparative Study of Zaitunah Subhan’s and Henri Shalahuddin’s Interpretations - Bannan Naelin Najihah; Hilda Yanti Safitri (Institut Agama Islam Persis Bandung, 2022)
This article discusses the comparison of the interpretations of Zaitunah Subhan (feminist Muslim) and Henri Salahuddin (conservative occidentalist Muslim) regarding inheritance verses. The lack of comparative studies of Muslim feminist and conservative Muslim interpretations of the inheritance verse encourages the importance of studying this matter. This study uses a qualitative comparative study method with a literature review approach. The data sources are the book